Home and Homelessness - Overcoming Dualism. Transcendence in the Work of Jan Cep - Seidel-Maczynska, Aleksandra (Bohemica Olomucensia, 2015)
The starting point of deliberations included in this article is Fucik's metaphor of ``dual home'', which has influenced the method of perception of Jan Cep's works and has put some emphasis on dualistic comprehension of all spatial and time categories in Cep's short stories. The aim of this article is to present a different moment of world's creation in Cep's works, especially in emigration short stories. Moreover, the aim is also to try to overcome the dual perception of reality and to add one more dimension - transcendence, which penetrates all space-time categories of Cep's worlds, therefore it puts all of them into metaphysical spheres. In the author's words, the reality is based on ``not easy balance'' of what is physical and spiritual, temporary and eternal, of what is placed ``here'' and ``there'', ``known'' and ``strange''. The world is not a clearly dualised structure but it is the world full of cracks, through which a second metaphysical reality is revealed. The world's base is a process, a never-ending movement between horizontal and vertical lines - and the point of their contact always means a violation of ontological structure of the world and the penetration of it by a mystery - God's transcendence.
Keywords: Cep's literary works; homelessness; dual home; emigration short stories; transcendence